2015
DOI: 10.1007/s13127-015-0232-8
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of North African foxes and population genetic dynamics in the desert—insights into the evolutionary history of two sister taxa, Vulpes rueppellii and Vulpes vulpes

Abstract: The effects of Pleistocene glaciations on moulding biodiversity have been extensively investigated within temperate biomes, yet arid ecosystems are largely neglected. A clear example comes from North Africa and the successive range of expansion/contraction cycles of the Sahara desert. This study focuses on North African foxes (genus Vulpes), in particular two sister taxa, Vulpes rueppellii and Vulpes vulpes, but also Vulpes zerda and Vulpes pallida. A set of two mitochondrial markers (Cyt-b and D-loop) and 31-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 97 publications
1
19
0
Order By: Relevance
“…Other studies, discussing mitochondrial DNA control region haplotypes identified in red fox from four regions in Croatia, revealed haplotype diversity of Croatian red foxes to be among the highest of all European red fox populations studied to date, although genetic differentiation among regions was quite low (Galov et al, 2014). As evidenced by analysis of the nuclear and mitochondrial markers, Eurasian red foxes also form a separate group in comparison to the representatives of Vulpes vulpes living in North Africa (Leite et al, 2015). While taking into consideration Asia Minor, the majority of Turkish haplotypes grouped with those of Eurasia.…”
Section: Introductionmentioning
confidence: 88%
“…Other studies, discussing mitochondrial DNA control region haplotypes identified in red fox from four regions in Croatia, revealed haplotype diversity of Croatian red foxes to be among the highest of all European red fox populations studied to date, although genetic differentiation among regions was quite low (Galov et al, 2014). As evidenced by analysis of the nuclear and mitochondrial markers, Eurasian red foxes also form a separate group in comparison to the representatives of Vulpes vulpes living in North Africa (Leite et al, 2015). While taking into consideration Asia Minor, the majority of Turkish haplotypes grouped with those of Eurasia.…”
Section: Introductionmentioning
confidence: 88%
“…Foxes are one of the most widespread carnivores; while they originated from the Middle East (Statham et al ., ), today they are present in all continents with the exception of Antarctica. Specifically, British foxes derived from Central European populations (Edwards et al ., ), North American foxes differ from their European counterparts (Sacks et al ., ; Leite et al ., ), while Australian foxes were introduced by humans from Europe (Macdonald & Reynolds, 2004). Cats were probably domesticated in the early Neolithic period (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…[139]. Similarly deep splits between Iberian and Maghrebian populations of the same species were PLOS ONE found in other terrestrial vertebrates, such as in amphibians, reptiles [25,140], and in mammals [141][142][143][144]. The Strait of Gibraltar was suggested to be an effective biogeographic barrier for trans-Mediterranean floral and faunal interchange [145][146][147] and accordingly split ages between populations north and south of the Strait were often dated to times when land bridges between the two continents existed, e.g.…”
Section: Phylogeographic Patterns In the Ibero-maghrebian And Cyrenaimentioning
confidence: 92%
“…Rather complex phylogeographic patterns have been documented for other mammals, e.g. vicariance of genetically distinct Red Fox populations (Vulpes vulpes) of the Maghreb and the Fertile Crescent that are replaced by Rueppell's Fox (Vulpes rueppellii) across their distribution gap in Libya [143]. In other mammal species, Sardinian and other Mediterranean island populations are firmly nested in a trans-Maghrebian clade (e.g.…”
Section: Phylogeographic Patterns In the Ibero-maghrebian And Cyrenaimentioning
confidence: 99%